The effect of subsidies, climate, and technology on residential electricity consumption in Qatar - Esmat Zaidan (16855203) (2025)
This paper examines the relationship between governmental subsidies, temperature changes, technological advancements, and residential electricity consumption in Qatar by using empirical analysis. This research aims to explore a topic that is rarely explored in current literature. It uses stochastic frontier analysis to measure energy efficiency and identify factors that cause inefficiencies in electricity consumption. The analysis considers the extent to which government subsidies affect residential electricity consumption, how changes in temperature influence electricity consumption in an economy sensitive to climate change, and how technology affects this consumption. The findings indicate that subsidy elasticity of electricity demand is positive, with a 1 % increase in subsidies leading to a 1.01 % rise in electricity consumption for flats. Reflecting Qatar's climate influence, temperature also correlates positively with usage. Technology has a minimal impact on demand, suggesting that improvements in energy efficiency can help reduce consumption. Our research highlights important policy implications, recommending changes to the current subsidy structure and efforts to improve energy efficiency in Qatar. Other Information Published in: Utilities Policy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jup.2025.101998